2009
DOI: 10.1080/12538078.2009.10516163
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin and fatty acid contents in seeds of some taxa belonging to genusLathyrusL. growing in Turkey

Abstract: Abstract.-In the present study, levels of vitamin and fatty acid composition in mature seeds of some Lathyrus L. taxa [L. roseus Stev., L. tuberosus L.,var. affinis (Guss.) Arcang.] were determined by using HPLC (high-performance liquid chromatography) and VPC (vapour gas chromatography). Palmitic acid (C16:0), stearic acid (C18:0), oleic acid (C18:1 n-9), linoleic acid (C18:2 n-6) and α-linolenic acid (C18:3 n-3) were found as major fatty acid components in all studied eleven taxa. In addition, δ-tocopherol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 32 publications
1
15
1
Order By: Relevance
“…The finding of our study indicate that retinol contents were lower than those reported for Lathyrus species studied by Sahin et al (2009). Ascorbic acid contents were higher than that reported for Lathyrus maritimus by Chavan et al (1999) but were similar to findings of Sahin et al (2009) and -carotene contents were found higher than that of Chavan et al (1999).…”
Section: Results and Dissussion Variability In Vitamin Contentscontrasting
confidence: 46%
See 2 more Smart Citations
“…The finding of our study indicate that retinol contents were lower than those reported for Lathyrus species studied by Sahin et al (2009). Ascorbic acid contents were higher than that reported for Lathyrus maritimus by Chavan et al (1999) but were similar to findings of Sahin et al (2009) and -carotene contents were found higher than that of Chavan et al (1999).…”
Section: Results and Dissussion Variability In Vitamin Contentscontrasting
confidence: 46%
“…Ascorbic acid contents were higher than that reported for Lathyrus maritimus by Chavan et al (1999) but were similar to findings of Sahin et al (2009) and -carotene contents were found higher than that of Chavan et al (1999). The vitamin content of plant species is related to certain factors, such as genetic features and ecological conditions (Munzuroglu et al, 2000).…”
Section: Results and Dissussion Variability In Vitamin Contentsmentioning
confidence: 52%
See 1 more Smart Citation
“…This fatty acid is reported as very constant lipid constituent in the most of the leguminous genera seed oil (Bağcı et al, 2004;Bağcı, 2006). Several studies from Leguminoseae reported that palmitic acid (C16:0) ranged 18.5-32.6% in the Astragalus (Adıgüzel et al, 2006), 3.8-19.4% in the Vicia (Akpınar et al, 2001) and 11.4-21.4% (Bağcı & Şahin, 2004;Şahin et al, 2009;Emre et al, 2010) in the Lathyrus taxa. Stearic acid is second major saturated fatty acid (2.9-7.1%).…”
Section: Resultsmentioning
confidence: 99%
“…Arslan (2017) indicated that legumes include K vitamin together with vitamin B1, B2, B6, vitamin C, vitamin E. Furthermore, it was found that studied O. species have high D3 content (66.7±1.2-36.7±1.1 µg/g) in this study. Sahin et al (2009) found that Lathyrus taxa, the other genus of legumes, have high vitamin D3. Also, they determined that Lathyrus has high δ-tocopherol, αtocopherol, α-tocopherol acetate contents (Sahin et al 2009).…”
Section: Discussionmentioning
confidence: 99%